Overview of public governance of public-private partnerships in the Russian Federation - Hawkesworth, Ian (OECD Publishing, 2016)
Good infrastructure is crucial to a country's development and continued success. Russia's developmental goals require new and upgraded infrastructure throughout its territory. Private investment in capital projects will be vital for Russia to meet these goals. To facilitate private investment, the Russian government has embarked on a series of reforms aimed at improving the investment climate and creating a robust institutional framework for private sector participation in concessions and Public-Private Partnerships (PPPs). The OECD's 2012 Council Recommendation on Principles for Public Governance of Public-Private Partnerships (the PPP Recommendation) aims to support governments facing trade-offs between three demands inherent in a PPP project process. This article provides an overview of the alignment of the policies of the Russian Federation in the area of public governance of PPPs with these recommendations. JEL classification: H41, H54, H57 Keywords: Council recommendations, public private partnerships, Russian Federation, value for money